Biomarker Records From Eocene Lacustrine Sequence in the Eastern Tibet Plateau and Its Implication for Organic Matter Sources - Wei, Jingyi; Wang, Yongli; Wang, Gen; Wei, Zhifu; He, Wei; Zhang, Ting; Ma, Xueyun; Zhang, Pengyuan; Ma, He; Yu, Xiaoli; Li, Shangkun; Li, Lun (Frontiers in Earth Science, 2022)
The Eocene is the initial stage of the Cenozoic global cooling. Compared with the abundant marine records, the continental records of Eocene are scarce. Throughout the Eocene, a series of continuous deposition of gypsum and volcanic tuff-bearing red clastic sediments have developed in the Nangqian Basin (NB). In this work, representative sediments were collected from the NB, and lipid biomarkers and compound-specific carbon isotopes of n-alkanes were analyzed. Based on the robust paleomagnetic age-depth model, from the early to the late Eocene, the compound-specific carbon isotopic compositions (δ13C23 and δ13C25) increased with the sedimentary facies changed. At the same time, the relative proportion of mid-chain length to long-chain length homologues (Paq) decreased and the peak carbon number (Cmax) shifted from nC21, nC22 or nC23 to nC16, nC25, nC27 or nC31. We ascribed these variations to the climate drying and water level turning high as indicated by the lithology change from fluvial to lacustrine facies, and the terrestrial inputs from neighboring mountain belts in the middle–late Eocene. Moreover, we compared our n-alkanes results with other records from the TP as well as the global sea level and marine benthic δ18O. We found that a nearly synchronous deformation and drying of the eastern TP caused by the India-Asia collision in the early Eocene closely related to the arid conditions and topographically changed in the northern TP. The climate variations in the Eocene in NB were mainly controlled by the global climate change and the uplift of the TP, and affected by the Paratethys Sea on a long scale.